Boletín meteorológico : Estación Experimental Agropecuaria Montecarlo. Enero 2023. - Silva, Fidelina; Visentini, Jorge Miguel; Kobs, Roberto Oscar; Costa, Marcos Ruben; Samudio, Marcial; Landaida, Cristian Alejandro; Lunatti, Diego Guillermo; Thiessen, Mario Gabriel; Sicardi, Hugo Orlando; Olinuck, Jose Angel (EEA Montecarlo, INTA, 2023)
EEA Montecarlo